Dialysis in Israeli Children between 1990 and 2020: Trends and International Comparisons. Issue 3 (20th March 2023) - Regev-Epstein, Lilach C.; Frishberg, Yaacov; Davidovits, Miriam; Landau, Daniel; Magen, Daniella; Weismann, Irit; Stern-Zimmer, Michal; Beckerman, Pazit; Keinan-Boker, Lital; Calderon-Margalit, Ronit; Vivante, Asaf
Visual Abstract: Abstract : Background: Childhood kidney failure is a rare condition with worldwide clinical variability. We used a nationwide multicenter analysis to study the pretransplant course of the entire Israeli pediatric kidney failure population over 30 years. Methods: In this nationwide, population-based, historical cohort study, we analyzed medical and demographic data of all children treated with KRT and reported to the Israeli kidney failure registry in 1990–2020. Statistical analysis was performed with incidence rate corrected for age, ethnicity, and calendar year, using the appropriate age-related general population as denominator. Results: During the last 30 years, childhood incidence of kidney failure decreased. Average incidence in 2015–2019 was 9.1 cases per million age-related population (pmarp). Arab and Druze children exhibited higher kidney failure incidence rates than Jewish children (18.4 versus 7.0 cases pmarp for minorities versus Jews). The most common kidney failure etiologies among Arab and Jewish children were congenital anomalies of the kidney and urinary tract (approximately 27%), followed by cystic kidney diseases among Arab children (13%) and glomerulonephritis among Jewish children (16%). The most common etiology among Druze children was primary hyperoxaluria type 1 (33%). Israel's national health insurance provides access to primary health care to all citizens. Accordingly, waiting time for deceased-donor transplantation was equal between all ethnicities. Living-donor kidney transplantation rates among minority populations remained low in comparison with Jews over the entire study period. Although all patient groups demonstrated improvement in survival, overall survival rates were mainly etiology dependent. Conclusions: In Israel, Arab and Druze children had a higher incidence of kidney failure, a unique etiological distribution, and a lower rate of living-donor kidney transplantations compared with Jewish children.